Parliament House (WA) Forecourt and Fountains Redevelopment - Pendal, Simon; Neille, Stephen (Simon Pendal and Stephen Neille, 2007)
Simon Pendal and Stephen Nellie have won a Department of Housing and Works competition to redesign the fountains and forecourt at Perth's Parliament House. They have also been chosen to exhibit In New Trends of Architecture in Europe and Asia-Pacific 2008- 2009.